(untitled) (BIRDEM Medical Journal, 2020)
Rapidly progressive glomerulonephritis is one of the most dramatic and tragic presentations of lupus nephritis (LN) or renal manifestation of systemic lupus erythematosus (SLE). A 35-year-old Bangladeshi gentleman presented with worsening oedema, scanty, high colored, frothy urine and deteriorating renal function. He had puffy face, anaemia, oedema, normal jugular venous pressure (JVP), high blood pressure (150/90 mm Hg), ascites and bilateral pleural effusions. Diagnostic work-up confirmed SLE with class IV LN. His initial response to specific therapy showed improvement Birdem Med J 2020; 10(2): 137-138